Organizational Culture as a Moderator in the Relationship Between Ethical Leadership, Ethical Culture, and Organizational Citizenship Behavior - Muhammad Donal Mon; Dewi; Agustinus Setyawan (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Ethical leadership and ethical culture have been widely recognized as important factors in promoting organizational citizenship behavior. However, the contextual role of organizational culture in shaping these relationships remains insufficiently understood. This study examined the relationships among ethical leadership, ethical culture, organizational citizenship behavior, and the moderating role of organizational culture. A quantitative explanatory research design was adopted. Data were collected from 331 employees in Batam, the majority of whom were aged 18–27 years, using purposive sampling through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that ethical leadership positively influenced ethical culture and organizational citizenship behavior, while ethical culture positively influenced organizational citizenship behavior. Organizational culture did not significantly moderate the relationship between ethical leadership and ethical culture. However, organizational culture significantly moderated the relationship between ethical culture and organizational citizenship behavior in an unexpected negative direction, indicating that the positive effect of ethical culture became weaker as organizational culture increased. These findings highlight the importance of ethical leadership in fostering ethical culture and encouraging organizational citizenship behavior while suggesting that the moderating role of organizational culture is more complex than originally hypothesized.